The Literature of American Library History, 2012-2013. - Goedeken, Edward A. (Information & Culture, 2016)
An essay is presented on the literature of American librairy history in 2012 to 2013. It looks at various literature including the books by Robert Post which explores the history of the Smithsonian Institution in Washington, D.C, Philip Gura on the detailed history of the American Antiquarian Society, and Alea Henle on the role of essayist Hannah Mather Crocker in collection and preserving the public library built by generations of the Mather family.